2016
DOI: 10.1038/srep36778
|View full text |Cite
|
Sign up to set email alerts
|

Larval nutritional stress affects vector life history traits and human malaria transmission

Abstract: Exposure to stress during an insect’s larval development can have carry-over effects on adult life history traits and susceptibility to pathogens. We investigated the effects of larval nutritional stress for the first time using field mosquito vectors and malaria parasites. In contrast to previous studies, we show that larval nutritional stress may affect human to mosquito transmission antagonistically: nutritionally deprived larvae showed lower parasite prevalence for only one gametocyte carrier; they also ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 61 publications
9
45
0
1
Order By: Relevance
“…Further, nutrient availability and daily temperature regimes can vary significantly among active breeding containers distributed in the same household area (Hemme et al, 2009). Despite shared genetic ancestry, larval stress has proven a critical influence on adult phenotype, which in turn is strikingly correlated with a suite of life history traits including vector competence (De Jesus and Reiskind, 2016; Honek, 1993; Mourya et al, 2004; Ponlawat and Harrington, 2007; Price et al, 2015; Schluter et al, 1991; Vantaux et al, 2016). In a previous study, our laboratory demonstrated the G × E influence of larval stress on adult body size (Schneider et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Further, nutrient availability and daily temperature regimes can vary significantly among active breeding containers distributed in the same household area (Hemme et al, 2009). Despite shared genetic ancestry, larval stress has proven a critical influence on adult phenotype, which in turn is strikingly correlated with a suite of life history traits including vector competence (De Jesus and Reiskind, 2016; Honek, 1993; Mourya et al, 2004; Ponlawat and Harrington, 2007; Price et al, 2015; Schluter et al, 1991; Vantaux et al, 2016). In a previous study, our laboratory demonstrated the G × E influence of larval stress on adult body size (Schneider et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Then, infectious humans remain infectious (Ih) during a period equals to 1/ on average. See parameter values in table supplement S1 (Roux et al 2015, Vantaux et al 2016. In our simulation we based the HBI of exposed mosquitoes ( s) on the confidence intervals of oocyst-infected mosquitoes that were experimentally measured in this study.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…It is an important factor regarding host-pathogen interactions; as host nutrition influences multiple measures of adult performance, immune response, and the resources necessary for pathogen replication (Lee et al 2006, 2008; Telang et al 2012, Yee et al 2015). Larval nutritional stress can reduce the immune response of mosquitoes allowing for increased pathogen infection (Sindbis virus; Muturi et al 2011) or reduce resources for pathogen development (malaria; Vantaux et al 2016ab). Further, nutritionally stressed larvae result in adults with reduced mass.…”
Section: Introductionmentioning
confidence: 99%